PERANCANGAN APLIKASI REKAM MEDIS BERBASIS ANDROID WEB SERVICE DENGAN MENGGUNAKAN RESTFUL API DI POLINDES DESA GOMBANG KECAMATAN SLAHUNG - Fredy Setyo Budi Utomo; Indah Puji Astuti; Moh Bhanu Setyawan (Universitas Muhammadiyah Ponorogo, 2020)
The Polindes Desa Gombang is a form of community participation in providing delivery assistance and community health services, including family planning, maternal and child health, and other health services. Currently, the Village Police of Gombang has several problems, such as the process of recording the exit and entry of drugs, data on the disease of patients who have been treated, making referral letters and medical records which only consist of patient data which if one of the patients is lost it will be troublesome. officers in that section in recap all data - data at the end of making the report. Due to the process of recording patient data, recording the entry and exit of drugs, making referral letters is still using the manual method, so this can cause no stored medical records and are vulnerable to loss because the recording process is only written or in a book. Based on this problem, it is proposed to create a system that uses web and android technology using the programming language PHP, Java and MY SQL Database. This system is able to handle recording patient data or the results of medical records that have been carried out, the patient's medical history, the number of drug stocks that are still available for the treatment of these patients and the making of referral letters.